2017
DOI: 10.1111/liv.13369
|View full text |Cite
|
Sign up to set email alerts
|

Low transferrin and high ferritin concentrations are associated with worse outcome in acute liver failure

Abstract: High ferritin and low transferrin levels are associated with worse outcome in patients with acute liver failure. A model incorporating age, MELD score and transferrin outperformed MELD score for 90-day overall survival of non-transplanted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 27 publications
4
30
0
Order By: Relevance
“…ALF was associated with high ferritin levels in our study (2). In our cohort, 75 of 102 patients had ferritin levels above 500 ng/mL (Table 1).…”
Section: High Ferritin Levels Are Not Only But Mostly Because Of Livementioning
confidence: 48%
See 1 more Smart Citation
“…ALF was associated with high ferritin levels in our study (2). In our cohort, 75 of 102 patients had ferritin levels above 500 ng/mL (Table 1).…”
Section: High Ferritin Levels Are Not Only But Mostly Because Of Livementioning
confidence: 48%
“…The authors thank Dr. Brito-Azevedo for his interest in our paper and the opportunity to look at our data from a different perspective (1,2). Haemophagocytic lymphohistiocytosis (HLH) is a rare condition, associated with defective termination of the immune system, leading to multiorgan failure.…”
Section: High Ferritin Levels Are Not Only But Mostly Because Of Livementioning
confidence: 99%
“…They concluded that high ferritin and low transferrin levels are associated with worse outcome in patients with ALF. 1 As well pointed by authors, ferritin is also associated with inflammatory conditions. However, extremely high levels may be associated with a specific inflammatory disease, the hemophagocytic lympho- It is important to keep HLH as differential diagnosis in mind.…”
Section: High Ferritin Concentration In Acute Liver Failure: the Top mentioning
confidence: 65%
“…Several researchers have suggested that modifications might be needed to improve the prognostic value of the MELD system. ( )…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have suggested that modifications might be needed to improve the prognostic value of the MELD system. (11,12) Although patients with ALF may have similar clinical manifestations, the initial symptoms are usually obscure. Furthermore, the time from liver insult to the presence of ALF varies greatly.…”
mentioning
confidence: 99%